2004
DOI: 10.1111/j.1559-1816.2004.tb01984.x
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptation and Extension of the Attitudes Toward Seeking Professional Psychological Help Scale1

Abstract: Despite its utility, several conceptual and methodological concerns are raised regarding Fischer and Turner's (1970) Attitudes Toward Seeking Professional Psychological Help Scale (ATSPPHS). These concerns were addressed in an adaptation and extension of the ATSPPHS using 208 adult volunteers. The new Inventory of Attitudes Toward Seeking Mental Health Services (IASMHS) consists of 24 items and 3 internally consistent factors: psychological openness, help‐seeking propensity, and indifference to stigma. We repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
317
1
34

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(363 citation statements)
references
References 52 publications
11
317
1
34
Order By: Relevance
“…Psychological openness represents an individual’s disposition to acknowledge psychological problems and to consider seeking professional help. The extent to which individuals are concerned about significant others opinion if they find out that they were receiving professional help is represented through the indifference to stigma subscale (Mackenzie, Knox, Gekoski, & Macaulay, 2004). Mackenzie et al (2004) demonstrated that IASHMS discriminates between participants who had and those who had not used mental health services.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological openness represents an individual’s disposition to acknowledge psychological problems and to consider seeking professional help. The extent to which individuals are concerned about significant others opinion if they find out that they were receiving professional help is represented through the indifference to stigma subscale (Mackenzie, Knox, Gekoski, & Macaulay, 2004). Mackenzie et al (2004) demonstrated that IASHMS discriminates between participants who had and those who had not used mental health services.…”
Section: Introductionmentioning
confidence: 99%
“…Among these dimensions, their empirical study further concluded that for those in need of services, affordability, availability, and accessibility are greater barriers than individuals' concerns about being stigmatized by others. In line with these arguments, Mackenzie et al (2004) also pointed out the weak relationship between indifference to stigma and help-seeking propensity which is complicated by factors such as "how busy individuals see themselves at any given time" (Mackenzie et al 2004(Mackenzie et al , p. 2428. These studies highlight the importance of understanding how individuals' beliefs about external control factors might affect help-seeking intentions and behaviors.…”
Section: Agency and Control Beliefs And Willingness Of Help Seeking-imentioning
confidence: 87%
“…An interesting finding revealed by our review of this area might speak to this complexity: The correlation between stigma toward mental illness and mental health service utilization is inconsistent across several different studies. While some argue that stigma dissuades help seeking (Hirai and Clum 2000;Vogel et al 2006;Fox et al 2013), others find an insignificant relationship between indifference to stigma and help-seeking propensity (Farina 2000;Mackenzie et al 2004;Golberstein et al 2008). Future empirical studies are needed to incorporate cultural aspects as well as the experiences of ethnic minority and immigrant children and families, to better explore the complex mechanisms of how stigma toward mental health treatment impacts service utilization.…”
Section: Beliefs and Expectations About The Efficacy Of Professional mentioning
confidence: 99%
See 2 more Smart Citations